(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The economic importance of camels in the southern arid regions is very high. Domestic camels are highly valued by locals for their amazing features. First of all, the enormous endurance of these animals is striking. It manifests itself not only in the ability to do without water for a long time. For thousands of years, the power of many states of the East literally depended on camels. Only these animals could overcome the endless deserts that cut off these countries from the rest of the world. The camel is usually called the “ship of the desert”. Meanwhile, the Arab peoples prefer to call ships “camels of the sea”. However, the camel is not only a transport. From time immemorial and to the present, camels have been used as draft power and bred for meat, milk, leather, wool and dung, that is, the animal is able to replace a ram, a horse and a cow. Camel meat is eaten, it is quite suitable for consumption and tastes a little sweet due to the presence of glycogen in it. Beshbarmak is prepared from camel meat, and fat from humps is consumed warm, immediately after slaughter, then it goes for distillation.